Neutrophils Are Decreased in Obsessive-Compulsive Disorder: Preliminary Investigation - Atmaca, Murad; Kilic, Faruk; Koseoglu, Filiz; Ustundag, Bilal (Korean Neuropsychiatric Assoc, 2011)
Objective There has been no study in the literature evaluating total blood count in obsessive-compulsive disorder (OCD). Therefore, we performed the present study to spesifically measure serum total blood count particularly white blood cells to see whether or not its eventual alterations might have an etiopathogenetic significance in patients with OCD. Methods Total blood count was measured in thirty patients and same number of healthy controls. Additionally, all patients were assessed by Yale-Brown Obsession Compulsion Scale (Y-BOCS). Results Except for neutrophil count, there were no significant differences between the groups regarding any haematological parameter. The mean neutrophil count of the patient group was lower compared to that of the control subjects. Conclusion In conclusion, the present study suggests that neutrophil count is reduced in pure OCD patients and this finding may contribute to the role of immunological factors in the pathogenesis of OCD. Psychiatry Investig 2011;8:362-365
Keywords: OCD; Total blood count; Neutrophil